2017
DOI: 10.5130/ajceb.v17i3.5482
|View full text |Cite
|
Sign up to set email alerts
|

Comparative empirical analysis of temporal relationships between construction investment and economic growth in the United States

Abstract: The majority of policymakers believe that investments in construction infrastructure would boost the economy of the United States (U.S.). They also assume that construction investment in infrastructure has similar impact on the economies of different U.S. states. In contrast, there have been studies showing the negative impact of construction activities on the economy. However, there has not been any research attempt to empirically test the temporal relationships between construction investment and economic gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The first strand deals with the relationship between construction sector and economic development [18,34,35]. The second strand deals with whether investment in construction sector drives gross domestic product (GDP) growth or vice versa [3,16]. Whereas the third strand deals with the pull and push effects of construction sector within the national economy through input-output analysis [36,37].…”
Section: Theoretical Framework and Empirical Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The first strand deals with the relationship between construction sector and economic development [18,34,35]. The second strand deals with whether investment in construction sector drives gross domestic product (GDP) growth or vice versa [3,16]. Whereas the third strand deals with the pull and push effects of construction sector within the national economy through input-output analysis [36,37].…”
Section: Theoretical Framework and Empirical Reviewmentioning
confidence: 99%
“…Empirically, scholars have expressed divergent views on whether public investments in construction sector propel economic growth or vice versa [16,20,26,[44][45][46][47], and especially in Nigeria [3,19,[48][49][50][51][52][53]. However, the perceived need of investments in construction sector is directly dependent on the state of economy and government fiscal and monetary policies [54].…”
Section: Theoretical Framework and Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Public investments in infrastructure affects the economic growth of a country (Bravo, 2014), positively influencing the industrialization processes (Rodríguez et al, 2016). Similarly, several studies have shown there is high correlation between investment in strategic sectors and GDP growth, as well as improvements in the general conditions of the economy (Ahmadi & Shahandashti, 2017;Galindo & Sosvilla, 2012). This would explain the evolution of the gross domestic product in the Andean country, since public spending in Ecuador exceeded in 2016 the tripled amount of the same as of 2007.…”
Section: Introductionmentioning
confidence: 98%
“…The construction sector, as an important sector in the economy of the United States (Ahmadi and Shahandashti, 2017), plays a vital role in the recovery phase of natural hazards (Lloyd-Jones, 2006; Jayaraj, 2006; Benson et al , 2007; Owen and Dumashie, 2007; Amaratunga and Haigh, 2008; UN/ISDR, 2009; Hallegatte, 2014; Ahmadi and Shahandashti, 2018). Moreover, most indirect economic losses in the aftermath of natural hazards are construction-related losses (Hallegatte, 2014).…”
Section: Introductionmentioning
confidence: 99%